Asticou's Island Domain: Wabanaki Peoples at Mount Desert Island 1500-2000 - Prins, Harald E. L.; McBride, Bunny (the Digital Archaeological Record)
This historical-ethnographic overview of Acadia National Park spans almost 500 years and covers a wide coastal stretch between Penobscot and Gouldsboro Bays – and sometimes much beyond. Such breadth of coverage is necessary in order to take in the park’s center piece on Mount Desert Island, plus Isle au Haut and Schoodic Peninsula, along with various land holding arrangements (including easements) on numerous offshore sea-islands in this area. The study explores the shifting but ongoing relationship between this habitat and Wabanaki peoples – a group of northeastern Algonquian- speaking ethnic groups or tribal nations today distinguished as the Abenaki, Maliseet, Mi'kmaq, Passamaquoddy and Penobscot.